2021
DOI: 10.1002/mrm.29004
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional quantification of circulation using finite‐element methods in four‐dimensional flow MR data of the thoracic aorta

Abstract: Purpose Three‐dimensional (3D) quantification of circulation using a Finite Elements methodology. Methods We validate our 3D method using an in‐silico arch model, for different mesh resolutions, image resolution and noise levels, and we compared this with a currently used 2D method. Finally, we evaluated the application of our methodology in 4D Flow MRI data of ascending aorta of six healthy volunteers, and six bicuspid aortic valve (BAV) patients, three with right and three with left handed flow, at peak syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Barker et al [ 58 ] reported that type 1 BAVs with RL-fusion are associated with significantly elevated WSS at focal regions in the AAo, and these regions correspond to the aortic jet impingement locations. Sotelo et al [ 27 ] have reported, through 4D flow MRI-based measurements, that BAV patients exhibit strong, positive axial circulation in the AAo which extends until the aortic arch. In comparison, healthy volunteers exhibited considerably weaker positive axial circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barker et al [ 58 ] reported that type 1 BAVs with RL-fusion are associated with significantly elevated WSS at focal regions in the AAo, and these regions correspond to the aortic jet impingement locations. Sotelo et al [ 27 ] have reported, through 4D flow MRI-based measurements, that BAV patients exhibit strong, positive axial circulation in the AAo which extends until the aortic arch. In comparison, healthy volunteers exhibited considerably weaker positive axial circulation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Dux-Santoy et al [ 26 ] compared WSS on the AAo in 46 BAV patients to 44 healthy volunteers using time-resolved 3D MRI and found that regions exposed to low and oscillating wall shear stress in BAV patients did not match those with the highest prevalence of dilation. In other studies, the group also showed, through cardiac MRI analysis and in silico modeling that BAV patients exhibited strong helical flows in the aorta, with increased axial circulation [ 27 ] and circumferential wall shear stress [ 28 ] compared to healthy controls. Further, they showed that the magnitude and circumferential component of the local WSS vector correlated strongly in BAV patients with the risk of AAo growth rate [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hemodynamic parameters and the diameters in the entire thoracic aorta were obtained based on a finite-element method described previously ( 32 36 ) ( Figure 1A ). To provide a ground for location-specific comparisons, 16 regions ( Figure 1D ) were semi-automatically selected.…”
Section: Methodsmentioning
confidence: 99%